The Pilgrim Model: Using Transactional Analysis to Explore the Spiritual Pathway Toward Meaning and Knowing. (July 2017) - Milnes, Peter
Transactional analysis is uniquely positioned to follow Berne's (1972) encouragement to use "ancient religious stories" (p. 438) in "understanding…spirituality and its complex interfaces with religiosity and religious psychopathology" (Mellacqua, 2016, p. 149). Although there have been some attempts to integrate transactional analysis with religion (e.g., James, 1981), TA still lacks an easy-to-use model that can be employed by all psychotherapists, regardless of their religious persuasion. Almost everyone has been influenced by religion, so it is important that therapists are confident venturing into this area. The author discusses the ancient Greek concept of knowing consisting of logoi (knowing through logic and science) and mythoi (knowing through religious stories) and then presents what he calls the pilgrim model, which is based on classical transactional analysis. This model can be used to work with people of all faiths and could provide a basis for further development of religious or spiritual transactional analysis.